Vaccine Interaction and Protection against Virulent Avian Metapneumovirus (aMPV) Challenge after Combined Administration of Newcastle Disease and aMPV Live Vaccines to Day-Old Turkeys - Caterina Lupini; Matteo Legnardi; Giulia Graziosi; Mattia Cecchinato; Valeria Listorti; Calogero Terregino; Elena Catelli (Vaccines, 2023)
Newcastle disease virus (NDV) and avian metapneumovirus (aMPV) are among the most impactful pathogens affecting the turkey industry. Since turkeys are routinely immunized against both diseases, the hatchery administration of the combined respective live vaccines would offer remarkable practical advantages. However, the compatibility of NDV and aMPV vaccines has not yet been experimentally demonstrated in this species. To address this issue, an aMPV subtype B live vaccine was administered to day-old poults either alone or in combination with one of two different ND vaccines. The birds were then challenged with a virulent aMPV subtype B strain, clinical signs were recorded and aMPV and NDV vaccine replication and humoral immune response were assessed. All results supported the absence of any interference hampering protection against aMPV, with no significant differences in terms of clinical scoring. In addition, the mean aMPV vaccine viral titers and antibody titers measured in the dual vaccinated groups were comparable or even higher than in the group vaccinated solely against aMPV. Lastly, based on the NDV viral and antibody titers, the combined aMPV and NDV vaccination does not seem to interfere with protection against NDV, although further studies involving an actual ND challenge will be necessary to fully demonstrate this hypothesis.